Notulae ad floram Sloveniae - Wraber, Tone (Hladnikia (Ljubljana), 1998)
First recorded in Slovenia; list of Cirsium-hybrids in Slovenia
Keywords: fitogeografija; flora; florae; phytogeography; Slovenia; Slovenija; vegetacija; vegetation